Pre-sowing treatment of leguminous seeds with a magnetic field: Effect on seed sowing indicators, crop structure and yield - Isakov A.N.; Ivanov I.V.; Savin M. I.; Sokolova L.A.; Chubarov F.L. (E3S Web of Conferences)
This study examined the effects of pre-sowing treatment of leguminous seeds with a constant inhomogeneous magnetic field on germination, crop structure, and yield through laboratory and field experiments. The research focused on fodder beans, asparagus beans, field peas, and narrow-leaved lupine. Parameters such as seed germination, root length, and germinal stem length of seedlings were monitored. A conveyor belt transported seeds through a magnetic field; the field's induction alternated direction four times, with an amplitude of 55 mT in the seed movement zone. Statistical analysis (p = 0.05) revealed that the magnetic field did not significantly affect seed germination, root length, or germinal stem length. Field studies corroborated these findings, showing no statistically significant differences between treated and untreated seeds in the number of beans per plant, seeds per bean, or seed mass per plant. Thus, the constant inhomogeneous magnetic field showed no statistically reliable effect on the sowing parameters, yield structure, or productivity of the tested leguminous crops in both laboratory and field experiments.